Effect of different growth conditions on physiological characteristics in two genotypes of Urochloa humidicola - Mayorga, Mildred; Cardoso Arango, Juan Andrés (CGIAR Initiative on Sustainable Animal Productivity, 2023)
The grass species Urochloa humidicola adapts to different environmental conditions, primarily waterlogging. Accession CIAT679 stands out for its adaptation to acidic soils of low fertility and easy propagation, while hybrid Uh08 1149 excels in agronomic characteristics and high capacity of Biological Nitrification Inhibition (BNI). This study aimed to evaluate physiological characteristics of these two U. humidicola genotypes in three contrasting growth conditions: hydroponic system, low-fertility soil, and high-fertility soil. CIAT679 genotype exhibited higher photosynthesis rate and biomass production, while hybrid Uh08 1149 had higher total nitrogen content in roots. Plants performed better photosynthetically and had higher biomass in the hydroponic system. In low-fertility soil, plants had better photosynthetic performance than in high-fertility soil; however, the latter exhibited greater biomass, possibly due to better root development.